Pengaruh Obat Kumur Beralkohol terhadap Kekasaran Permukaan Semen Ionomer Kaca Konvensional - Astrid Yudith (Jurnal Material Kedokteran Gigi, 2017)
Surface roughness is one of the important properties to determine the aesthetic and long-term durability of a dental restoration materials such as glass ionomer cements. In the oral cavity, the intervention of food, drink or other materials such as mouthwash can affect the properties of restorative materials. The aim of this study was to evaluate the effect of alcohol containing mouthwash to the surface roughness of conventional glass ionomer cement. This was an experimental laboratory study with time-series design. Samples were conventional glass ionomer cement (Fuji IX, GC, Japan) in disk shaped with 10 mm in diameter and 2 mm thick. Totally 10 samples were made and measured the initial surface roughness. Then the samples were stored in the alcohol containing mouthwash (Listerine® Cool Mint, Johnson & Johnson, Indonesia) for 30 seconds and measured the surface roughness again. The treatment and surface roughness measurements of samples is repeated up to 2 times for data 60 and 90 seconds. Roughness measurements made using profilometer tester (Mitutoyo, Japan). Data were analyzed by one-way ANOVA (p=0,05) post hoc LSD. The results showed the average value of surface roughness of glass ionomer cements early, after soaking 30, 60, and 90 seconds of 0.56 ± 0.11 µm, 0.71 µm ± 0.23, 0.96 ± 0.16 µm and 1.02 ± 0.13 µm. Data analysis shows the difference in surface roughness values were significantly (p <0.05) between groups immersion and significant difference was found between groups of 30 seconds to 60 seconds and a group of 60 seconds to 90 seconds. The conclusion that there is influence of alcoholic mouthwash to the surface roughness of glass ionomer cement and the longer the soaking time with a mouthwash that contains alcohol, the surface roughness of glass ionomer cement will increase.